(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2026)
We analyze a nonlinear compartmental model describing bird flu transmission dynamics within a poultry farm, incorporating susceptible, infectious, and removed compartments with vaccination. The basic reproduction number R0 is derived, and the local stability of the disease-free and endemic equilibrium is investigated using linearization techniques. Bifurcation analysis based on standard bifurcation theory is conducted to identify parameter leading to qualitative changes in disease dynamics, revealing the occurrence of a forward transcritical bifurcation. Numerical simulations are used to illustrate threshold behavior and assess the impact of vaccination as a mitigation strategy on outbreak persistence. The results provide insights into control thresholds and the design of effective on-farm intervention strategies